1996
DOI: 10.1177/000992289603500702
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms and Diabetes Mellitus in Children and Adolescents

Abstract: Because it may be difficult to evaluate gastrointestinal diseases in children with insulin-dependent diabetes mellitus (IDDM), this report highlights several clinical features unique to diabetes and emphasizes the relationship between gastrointestinal pathology and glycemic control. Two children with IDDM are described whose hyperglycemia, ketosis, and abdominal pain were the presenting features of H. pylori-positive duodenal ulcer disease and acute appendicitis, respectively. A third nondiabetic child develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(2 reference statements)
0
3
1
Order By: Relevance
“…Contrary to what has been found in studies of adults with diabetes (Bair et al, 2010; Van Acker et al, 2009; Vogiatzi et al, 1996), this investigation yielded few predictors of pain. Overall, the sample was relatively healthy, with the majority of children and adolescents self-reporting three or more days a week of exercising.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Contrary to what has been found in studies of adults with diabetes (Bair et al, 2010; Van Acker et al, 2009; Vogiatzi et al, 1996), this investigation yielded few predictors of pain. Overall, the sample was relatively healthy, with the majority of children and adolescents self-reporting three or more days a week of exercising.…”
Section: Discussioncontrasting
confidence: 92%
“…Other reports of recurrent pain in children and adolescents with T1DM are largely found in the literature as case studies. These reports have suggested that GI symptoms and T1DM are interrelated and, furthermore, that children and adolescents can present with a wide variety of GI symptoms (Schindler and Kowlessar, 1988; Vogiatzi et al, 1996). Contrary to the case study reports, one larger study failed to demonstrate differences in the frequency of GI symptoms between children and adolescents with T1DM versus a control group (Vazeou et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An autonomic neuropathy (3,4) and acute hyperglycemia (5,6) have been implicated in the pathogenesis. In children with T1DM, gastrointestinal symptoms are frequently seen, although their pathophysiology and impact on diabetes control are poorly defined (7)(8)(9). The aim of this study was to define the etiological role of autonomic neuropathy and potential motility impairment in children and adolescents with T1DM and gastrointestinal symptoms.…”
Section: Introductionmentioning
confidence: 99%